KJB the book that changed the world - Rhys-Davies, John.; Dionisotti, Paola, 1946-; Gregor, Simon; Rothney, Andrew; Stone, Norman; Watts, Murray; Lions Gate Entertainment (Firm); 1A Productions (Firm) (Santa Monica, Calif. : Lionsgate, 2011)
"Acclaimed actor John Rhys-Davies visits landmarks, explains relics, and leads us back into a darker time to discover this fascinating tale of saints and sinners, power and passion, as the greatest translation of Holy Scripture emerges into a world and culture that would never be quite the same again"--Container.
Elizabeth's successor -- A crowned head -- Long live the king -- Young James -- Questioning Buchanan -- Finding his queen -- New king, old foes -- Theological revolution -- A new translation -- Catholic discontent -- Gun Powder Plot --Fawkes' demise -- Final draft -- James' memorial.
DVD, widescreen.
Closed-captioned.
English or Spanish subtitles.
Presenter, John Rhys-Davies.
Paola Dionisotti, Simon Gregor, Andrew Rothney.
Directors of photography, Michael Fox and Stephen Brand ; editor, Colin Goudie ; music, Jeremy Soule.
Keywords: Bible. -- Versions -- Authorized; Bible. -- Versions -- Authorized -- Drama; Bible. -- History; Bible. -- Influence; Great Britain -- History -- James I, 1603-1625.; Great Britain -- History -- James I, 1603-1625 -- Drama; Nonfiction films; Feature films; Historical films; Religious films; Video recordings for the hearing impaired